2011
DOI: 10.1007/s10886-011-9994-4
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Antofine from Invasive Swallow-Worts

Abstract: Pale swallow-wort (Vincetoxicum rossicum) and black swallow-wort (V. nigrum) are two emerging invasive plant species in the northeastern United States and southeastern Canada that have shown rapid population expansion over the past 20 years. Using bioassay-guided fractionation, the known phytochemical phenanthroindolizidine alkaloid, (-)-antofine, was identified as a potent phytotoxin in roots, leaves, and seeds of both swallow-wort species. In seedling bioassays, (-)-antofine, at μM concentrations, resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…[12] also showed that V. pumilum contained antofine and antofine N-oxide. Furthermore, antofine was found in V. nigrum and V. rossicum in different studies by some authors [8,13,30].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[12] also showed that V. pumilum contained antofine and antofine N-oxide. Furthermore, antofine was found in V. nigrum and V. rossicum in different studies by some authors [8,13,30].…”
Section: Discussionmentioning
confidence: 90%
“…Barb., V. stocksii and V. hirundinaria species including antibacterial and antifungal [8], antidiarrheal, antispazmodic [9], antileishmanial, antimalarial [5], cytotoxic [10], antifeedant and growth inhibition [7] effects in the literature. Phytochemical investigations revealed the presence of phenanthroindolizidine alkaloids [8,[10][11][12][13], steroidal glycosides [7,14,15], triterpenoids [15,16], flavonoids, saponins, phenolics [7,9], steroids [6,15], volatile compounds, acetophenone [6] and alkanols [15] in Vincetoxicum species. In these phytochemical constituents, phenanthroindolizidine alkaloids are characteristic secondary metabolites of some Asclepiadaceae and Moraceae genera including Cynanchum L., Vincetoxicum, Tylophora R.…”
Section: Introductionmentioning
confidence: 99%
“…Barb. and V. nigrum [21,22]; antifungal, antibacterial [12,23], antileishmanial and antimalarial activities of V. stocksii [12] and antioxidant activity of V. lutea L. [11] have been determined. Furthermore, cytotoxic [24,25], antifeedant and growth inhibition [26][27][28] effects of the genus were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigations revealed the presence of triterpenoids [13,15], phenanthroindolizidine alkaloids [21,22,25], steroids [15] and sugars [27,29] in whole parts of the Vincetoxicum species. Moreover, acetophenone, volatile compounds [13], starch [27] and saponins [27,30] were detected from the roots, and alkanols [15] and tannins [28] were detected from the aerial parts.…”
Section: Introductionmentioning
confidence: 99%
“…Dog-strangling vine has the ability to establish dense monocultures in invaded sites due to advantageous properties that include a polyembryony, tolerance of a wide range of environmental conditions, unique phytochemistry providing antifeedant/pathogenic protection, as well as the ability to be preferentially colonized by beneficial AMF relative to local native plants (Greipsson and DiTommaso 2006, Mogg et al 2008, Blanchard et al 2010, Douglass et al 2011, Gibson and Krasnoff 2011, Bongard et al 2013. Dog-strangling vine has the ability to establish dense monocultures in invaded sites due to advantageous properties that include a polyembryony, tolerance of a wide range of environmental conditions, unique phytochemistry providing antifeedant/pathogenic protection, as well as the ability to be preferentially colonized by beneficial AMF relative to local native plants (Greipsson and DiTommaso 2006, Mogg et al 2008, Blanchard et al 2010, Douglass et al 2011, Gibson and Krasnoff 2011, Bongard et al 2013.…”
mentioning
confidence: 99%